Throw technique biomechanics in competitive wrestling - Matveev, D. A.; Potsipun, A. A.; Oshina, O. V.; Levitsky, A. G. (Theory and Practice of Physical Culture, 2018)
The study analyzes the throw technique biomechanics in the modern competitive combat sports based on the authors` classification of throws into four groups including: coupled force; lever; block and combined groups, with each group supported by the relevant elementary physics driven model, and the combined group applying the combined model. The action scheme implies the following five phases: grabbling phase; body mass center shifting (imbalance) phase; pre-throw phase; throw execution phase; and the follow-up phase. The proposed scheme applies a movement algorithm with the relevant mechanical values to: